Isolation of mesenchymal stem cells from Pap smear samples - Park, Junghyun; Son, Daryeon; Hong, Wonjun; Jang, Jihoon; Cho, Geum Joon; Song, Gwonhwa; Kim, In Yong; You, Seungkwon (Obstetrics & gynecology science, 2020)
Exploiting their ability to differentiate into mesenchymal lineages like cartilage, bone, fat, and muscle, and to elicit paracrine effects, mesenchymal stem cells (MSCs) are widely used in clinical settings to treat tissue injuries and autoimmune disorders. One of accessible sources of MSC is the samples used for Papanicolaou (Pap) test, which is a cervical screening method for detecting potentially pre-cancerous and cancerous alterations in the cervical cells and to diagnose genetic abnormalities in fetuses. This study aimed to identify and isolate the stem cells from Pap smear samples collected from pregnant women, and to trace the origin of these cells to maternal or fetal tissue, and characterize their stem cell properties.OBJECTIVEExploiting their ability to differentiate into mesenchymal lineages like cartilage, bone, fat, and muscle, and to elicit paracrine effects, mesenchymal stem cells (MSCs) are widely used in clinical settings to treat tissue injuries and autoimmune disorders. One of accessible sources of MSC is the samples used for Papanicolaou (Pap) test, which is a cervical screening method for detecting potentially pre-cancerous and cancerous alterations in the cervical cells and to diagnose genetic abnormalities in fetuses. This study aimed to identify and isolate the stem cells from Pap smear samples collected from pregnant women, and to trace the origin of these cells to maternal or fetal tissue, and characterize their stem cell properties.To investigate the possibility and efficiency of establishing MSC lines from the Pap smear samples, we were able to establish 6 cell lines from Pap smear samples from 60 pregnant women at different stages of gestation.METHODSTo investigate the possibility and efficiency of establishing MSC lines from the Pap smear samples, we were able to establish 6 cell lines from Pap smear samples from 60 pregnant women at different stages of gestation.The 3 cell lines randomly selected among the 6 established in this study, displayed high proliferation rates, several characteristics of MSCs, and the capacity to differentiate into adipocytes, osteocytes, and chondrocytes. Our study identified that the stem cell lines obtainable from Pap smear sampling were uterine cervical stromal cells (UCSCs) and had 10% efficiency of establishment.RESULTSThe 3 cell lines randomly selected among the 6 established in this study, displayed high proliferation rates, several characteristics of MSCs, and the capacity to differentiate into adipocytes, osteocytes, and chondrocytes. Our study identified that the stem cell lines obtainable from Pap smear sampling were uterine cervical stromal cells (UCSCs) and had 10% efficiency of establishment.Despite their low efficiency of establishment, human UCSCs from Pap smear samples can become a simple, safe, low-cost, and donor-specific source of MSCs for stem cell therapy and regenerative medicine.CONCLUSIONDespite their low efficiency of establishment, human UCSCs from Pap smear samples can become a simple, safe, low-cost, and donor-specific source of MSCs for stem cell therapy and regenerative medicine.